Colorectal cancer in the north and south of Ireland 1950-1984. Issue 3 (September 1990) - Kee, F; Patterson, C; Collins, B
Abstract : STUDY OBJECTIVE--Northern Ireland has the highest standardised mortality ratios for colon cancer in the United Kingdom and the Republic of Ireland has some of the highest mortality rates for cancer in the world. The aim of the study therefore was to investigate trends in colorectal cancer in the north and south of Ireland over the period 1950 to 1984. DESIGN--The study was a cohort analysis of deaths from colorectal cancer for ages 35-74 years by five year age groups, divided by sex. SETTING--This was a population study involving all cases reported to the Registrar General of Northern Ireland and the Eire Vital Statistics and Central Statistical Office during the study period. MEASUREMENTS AND MAIN RESULTS--As in mainland Britain, rectal cancer mortality declined in the north and the south during the study period, but the fall began sooner for males than females. Colon cancer mortality fell in the late 1950s but subsequently rose to its previous high levels. CONCLUSIONS--The observation that there were declines in mortality in the north and south of Ireland in the late 1950s does not support the hypothesis that altered diet due to war rationing in Great Britain and Northern Ireland underlay the fall in British colon cancer mortality after the war. The very high standardised mortality ratios for colon cancer in Northern Ireland highlight a continuing major public health problem in the region.